An Analysis of Compound Words Found in The Encanto Movie Soundtrack - Isabela, Windi Apriyani; Tuminah, Tuminah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This research aims to identify the types of compound words and examine how their meanings are formed in the lyrics of the Encanto movie soundtrack. The analysis is based on Lieber’s (2009) theory for morphological classification, which divides compounds into endocentric and exocentric types, and Saeed’s (2016) theory for semantic classification, which distinguishes between transparent and opaque meanings. This study uses a descriptive qualitative method with documentation as the data collection technique. The steps include listening to the songs, checking the lyrics, identifying compound words, and classifying them based on their structure and meaning. The results show a total of 30 compound words: 24 (80%) are endocentric and 6 (20%) are exocentric; 23 (77%) have transparent meanings, while 7 (23%) are opaque. This study highlights the structural and semantic features of compound words found in song lyrics and shows how linguistic elements can enrich musical expression